Типи теплотехнічних споруд та температура випалювання кераміки у носіїв роменської культури - Пуголовок, Ю.О. (Археологія і давня історія України, 2022)
У статті розглянуто питання пов’язані із процесом випалюванням ліпленого посуду сіверян. На
підставі аналізу відомої джерельної бази та нових міждисциплінарних досліджень, виділяється кілька
типів теплотехнічних споруд, які використовували для цього процесу. На основі експериментальних
дослідження виділено температуру випалювання ліпленого посуду. The paper deals with the firing process of Romny culture
ceramics. One of the key operations in the manufacture of pottery
is the thermal effect on it. Firing is the last stage in pottery
production when ceramics acquire the necessary physical
properties and become suitable for use in various household
needs.
Analysis of the source and the results of interdisciplinary
research allows us to identify the thermal facilities used for
this process. It is also possible to determine the firing temperature
of handmade pottery.
It can be argued that Siverians handmade pottery burned
mainly in fires and kilns. Ordinary household stoves were
not used for this purpose. The firing was carried out mainly
without temperature exposure, for a short time, at low temperatures.
This assumption is supported by the color of the
shard at the break, as well as the presence of organic matter
traces or unmelted prints of organic on ceramic. Despite the
fact that clay products were burned at relatively low temperatures
during the period under study they were used in everyday
life. The firing temperature of Romny culture ceramics
had limits between 450 and 550 °С, in some cases reaching
600—800 °С.
The use of pottery kilns had to be followed by a special firing
regime. The time of their appearance probably lies within the
9th century, but this date needs to be clarified. Somewhat later,
in the 10th century two-chamber kiln structures appeared on
the Siverians settlements. The spread of such kilns is associated
with the influence of the Khazar Khaganate population. The
appearance of special kilns indicates a certain increase in economic
and production potential, which leads to the beginning of
the allocation of pottery in a separate branch of the craft.